Cyanide-free electrolytic gold plating solution

By selectively adsorbing the through-hole convex part using cationic surfactant in cyanide-free electrolytic gold plating solution, the problem of difficulty in precipitating the gold plating coating at the bottom of the through-hole is solved, and a more efficient gold plating coating formation is achieved.

CN115244221BActive Publication Date: 2025-05-02MATSUDA SANGYO
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202280002516.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-11-11
Filing Date
2022-03-10
Publication Date
2025-05-02
Estimated Expiration
2042-03-10

AI Technical Summary

Technical Problem

The existing cyanide-free electrolytic gold plating solution has difficulties in improving the precipitation of gold-plating coatings at the bottom of the through-hole, especially in through-holes with high aspect ratios.

Method used

By adding cationic surfactant to the cyanide-free electrolytic gold plating solution, it is selectively adsorbed on the convex portion of the through hole, inhibiting the precipitation of gold and promoting the precipitation of gold to the bottom of the through hole.

Benefits of technology

The precipitation rate of gold toward the bottom of the through-hole is significantly improved, ensuring that the gold-plated coating is fully formed at the bottom of the through-hole, and the gold-plated coating is fully formed on the side walls of the through-hole.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003777877000000081
    Figure BDA0003777877000000081
  • Figure HDA0003777883010000011
    Figure HDA0003777883010000011
Patent Text Reader

Abstract

The problem is to provide a cyanide-free electrolytic gold plating solution that can improve the deposition of gold at the bottom of a through hole. This problem is solved by a cyanide-free electrolytic gold plating solution containing an alkali metal gold sulfite salt, a water-soluble amine, a crystal modifier, and a cationic surfactant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a cyanide-free electrolytic gold plating solution. Background Art

[0002] Cyanide-free (intentionally cyanide-free) electrolytic gold plating solution is used when making wiring materials in semiconductor devices. Electrolytic gold plating solution uses potassium gold cyanide as a gold source, but cyanide compounds are highly toxic and corrode resists, so cyanide-free gold sources are generally used in semiconductor devices, such as electrolytic gold plating solutions containing alkali metal gold sulfite, ammonium gold sulfite, etc.

[0003] Patent Document 1 discloses a cyanide-free electrolytic gold plating solution for forming bumps, which contains an alkali metal gold sulfite or ammonium gold sulfite as a gold source, a water-soluble amine as a stabilizer, a crystal modifier, a sulfite and a sulfate as a conductive salt, a buffer, a polyalkylene glycol and / or an amphoteric surfactant. In addition, Patent Document 2 discloses a cyanide-free electrolytic gold plating solution in which the average molecular weight of the polyalkylene glycol is also specified.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2007-92156

[0007] Patent Document 2: Japanese Patent Application Publication No. 2008-115450 Summary of the invention

[0008] Problems to be solved by the invention

[0009] Cyanide-free electrolytic gold plating solution is widely used as a wiring material in semiconductor devices using substrates such as Si and GaAs. There are through holes (wiring) for connecting conductor layers, and a gold-plated film is applied from the side wall to the bottom of the through hole. In recent years, the demand for a high aspect ratio of through holes has increased, and there is a problem that it is difficult to precipitate gold plating at the bottom of the through hole.

[0010] In view of the above problems, an object of the present invention is to provide a cyanide-free electrolytic gold plating solution capable of improving the deposition of gold at the bottom of a through-hole.

[0011] Means used to solve problems

[0012] The present inventors have repeatedly conducted research to solve the above problems, and as a result, have obtained the following findings: the surfactant in the cyanide-free electrolytic gold plating solution contributes to the ease of gold precipitation in relation to the shape of the plated object. More specifically, it has been found that the cationic surfactant selectively adsorbs on the protrusions of the plated object to inhibit the precipitation of gold. Based on this finding, one embodiment of the present invention is a cyanide-free electrolytic gold plating solution containing an alkali metal gold sulfite salt, a water-soluble amine, a crystallization modifier, and a cationic surfactant.

[0013] Effects of the Invention

[0014] According to the present invention, it is possible to provide a cyanide-free electrolytic gold plating solution capable of improving the deposition of gold at the bottom of a through-hole. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] [ Figure 1 ] Figure 1 A schematic cross-sectional view of a general through hole in a semiconductor device. DETAILED DESCRIPTION

[0016] Hereinafter, the present invention will be described in detail. The description of the constituent elements described below is an example (representative example) of an embodiment of the present invention, and the present invention is not limited to these contents, and various modifications can be made within the scope of the gist of the present invention.

[0017] The present invention is directed to a cyanide-free electrolytic gold plating solution (hereinafter sometimes referred to as electrolytic gold plating solution) containing an alkali metal gold sulfite salt, a water-soluble amine, a crystal modifier, and a cationic surfactant. The cationic surfactant contained in the electrolytic gold plating solution is selectively adsorbed on the surface of the substrate. Figure 1 The gold plated film is formed on the convex part (the corner formed by the outermost surface and the side wall) of the through hole shown in the figure, thereby suppressing the precipitation of gold on the convex part and promoting the precipitation of gold to the bottom of the through hole (formation of the gold plated film). In addition, since the bottom of the through hole is the most difficult part for gold to precipitate, if the gold plated film is formed on the bottom, the gold plated film is also fully formed on the side wall of the through hole.

[0018] The mechanism by which the cationic surfactant in the electrolytic gold plating solution is selectively adsorbed on the protrusions of the plated object is not yet clear, but it is believed that the protrusions have the highest current density when electricity is applied, and the positively charged cationic surfactant is easily adsorbed by electrostatic action.

[0019] The cationic surfactant is not particularly limited, but is preferably a quaternary ammonium salt or an aliphatic amine. Examples of the quaternary ammonium salt include benzethonium chloride, cetylpyridinium chloride, Monohydrate, 1-dodecylpyridinium chloride As the aliphatic amine, there can be mentioned laurylamine sulfate, n-octylamine hydrochloride, laurylamine hydrochloride, etc. In addition, either or both of a quaternary ammonium salt and an aliphatic amine may be contained.

[0020] In this embodiment, the concentration of the cationic surfactant in the electrolytic gold plating solution is not particularly limited, but is preferably 0.01 mg / L or more and 10 mg / L or less, and more preferably 0.1 mg / L or more and 5 mg / L or less. When the concentration of the cationic surfactant increases, it can be seen that the hardness of the gold-plated film tends to increase. When it is less than 0.01 mg / L, sometimes the precipitation of gold to the bottom of the through hole is insufficient, and on the other hand, when it is greater than 10 mg / L, sometimes the crystal state changes.

[0021] In the electrolytic gold plating solution, the gold sulfite alkali metal salt is a substance used as a gold source, and its composition is not particularly limited, and examples thereof include sodium gold sulfite, potassium gold sulfite, ammonium gold sulfite, etc. Sodium gold sulfite is particularly preferred. In addition, in the electrolytic gold plating solution, the concentration of the gold sulfite alkali metal salt is not particularly limited, and is usually converted into a gold concentration of 5 g / L or more and 15 g / L or less, preferably 7 g / L or more and 13 g / L or less.

[0022] In the electrolytic gold plating solution, the water-soluble amine is a substance used as a stabilizer, and there is no particular restriction on its composition. For example, triethanolamine, ethylenediaminetetraacetic acid, ethane-1,2-diamine, etc. can be cited, and ethane-1,2-diamine is particularly preferred. By containing a stabilizer, the gold complex has a stabilizing effect. In addition, in the electrolytic gold plating solution, there is no particular restriction on the concentration of the water-soluble amine, which is usually 5 g / L or more and 20 g / L or less, preferably 7 g / L or more and 15 g / L or less.

[0023] In the electrolytic gold plating solution, as a crystallization modifier, Tl compounds, Pb compounds, As compounds, etc. can be listed, and thallium formate, thallium sulfate, and lead acetate are particularly preferred. By containing a crystallization modifier, the orientation of the resulting gold-plated coating and the adjustment of the crystallite size become easy. In addition, in the electrolytic gold plating solution, there is no particular restriction on the concentration of the crystallization modifier, which is usually 5 mg / L or more and 50 mg / L or less, preferably 10 mg / L or more and 30 mg / L or less.

[0024] In this embodiment, the surface tension of the cyanide-free electrolytic gold plating solution is preferably less than 60mN / m. If the surface tension of the electrolytic gold plating solution is less than 60mN / m, it is expected that the precipitation of gold plating to the bottom of the through hole will be further improved. In the present disclosure, the surface tension can be measured using the Du Noüy (hanging ring) method adopted in JIS-K-2241 (2017).

[0025] There is no particular limitation on the preparation method of the electrolytic gold plating solution involved in the present embodiment. It can be prepared by adding alkali metal gold sulfite, water-soluble amine, crystallization regulator, and cationic surfactant to an aqueous solvent containing water and mixing. In addition, it can also contain other ingredients that can be contained in the electrolytic gold plating solution, such as conductive salt, pH regulator (buffer), complexing agent, masking agent, etc. By adding conductive salt, the effect of improving uniform electrodeposition can be obtained. By adding complexing agent, the stability of the electrolytic gold plating solution can be improved. By adding pH regulator (buffer), it has the effect of suppressing local pH changes. By adding masking agent, it has the effect of suppressing the deterioration of coating appearance and hardness change.

[0026] The component analysis of the cationic surfactant in the electrolytic gold plating solution can be measured by liquid chromatography. In addition, the concentration of the cationic surfactant in the electrolytic gold plating solution can be measured by liquid chromatography.

[0027] [Example]

[0028] Hereinafter, the present invention will be described in more detail using examples, but the scope of the present invention is of course not limited to the description of the examples.

[0029] <Electrolytic gold plating bath construction>

[0030] A cyanide-free electrolytic gold plating solution containing 12 g / L gold (I) sodium sulfite as a gold concentration, 70 g / L sodium sulfite as an electrolyte, 10 g / L ethane-1,2-diamine as a stabilizer, 20 mg / L (thallium concentration) of thallium formate as a crystallization modifier, and various surfactants shown in Table 1 was prepared.

[0031] <Plating conditions: for buried through holes>

[0032] A substrate (base: nickel plating 2 μm, strike gold plating 0.02 μm) with a through hole (diameter: 100 μm, depth: 60 μm) was immersed in the electrolytic gold plating solution (liquid temperature 50°C, pH 8.0) for 18 minutes at a current density of 0.5 A / dm 2 Electrolytic gold plating is performed, followed by water washing and drying.

[0033] <Plating conditions: for hardness measurement>

[0034] The substrate (base: nickel plating 2 μm, strike gold plating 0.02 μm) was immersed in the electrolytic gold plating solution (liquid temperature 52° C., pH 7.8) for 36 minutes at a current density of 0.5 A / dm 2 Electrolytic gold plating is performed, followed by water washing and drying.

[0035] <Measurement of surface tension>

[0036] The surface tension was measured using the Du Noüy method adopted in JIS-K-2241. An electrolytic gold plating solution was added to a petri dish, a platinum ring was immersed in the plating solution, and the platinum ring was slowly separated from the plating solution in a vertical direction. The maximum value of the force required to separate the platinum ring was measured and calculated as the surface tension.

[0037] <Film thickness evaluation method>

[0038] For the through-holes of the substrate subjected to electrolytic gold plating, a cross-section polisher was used to form a cross section, and the thickness of the gold film was measured from the cross section using a scanning electron microscope. The thickness of the electrolytic gold plating film on the outermost surface of the substrate and the bottom of the through-hole were measured respectively, and the film thickness ratio (bottom of through-hole / outermost surface) was calculated.

[0039] <Particles in liquid>

[0040] In the case of unstable electrolytic gold plating liquid, the number of particles tends to increase due to the precipitation of gold particles and chemical components over time, so the number of particles in the liquid is also analyzed. As an analysis method, the electrolytic gold plating liquid in the bath is filtered using a 0.1μm membrane filter, and then the number of particles larger than 0.5μm is evaluated using a particle counter for the static liquid. Then, the case where the particles in the liquid are less than 200 / mL is evaluated as good, and the case where they are more than 200 / mL is evaluated as poor.

[0041] <Appearance evaluation of electrolytic gold plating film>

[0042] The surface of the substrate subjected to the electrolytic gold plating was visually observed to determine whether it was matte or semi-glossy.

[0043] <Hardness measurement of electrolytic gold plating film>

[0044] The Vickers hardness of the electrolytic gold-plated film is measured by heat treatment at 300°C for 30 minutes in the atmosphere. A microhardness tester (Mitutoyo Co., Ltd., HM-221) is used to measure the hardness of the electrolytic gold-plated film before and after the heat treatment 5 times using a Vickers indenter, and the average value is calculated. It should be noted that the hardness of the electrolytic gold-plated film is measured by applying a load to the indenter to form an indentation on the plated film, and the hardness is calculated from the diagonal of the indentation. Therefore, when the film thickness is thin, it may be affected by the base matrix. Therefore, in order to avoid the influence from the base, the film thickness of the electrolytic gold-plated film is set to be more than 10 μm.

[0045] (Examples 1 to 6)

[0046] Using benzethonium chloride (cationic surfactant) as a surfactant, electrolytic gold plating solutions with a surfactant concentration of 0.01 mg / L (Example 1), an electrolytic gold plating solution with a surfactant concentration of 0.1 mg / L (Example 2), an electrolytic gold plating solution with a surfactant concentration of 1 mg / L (Example 3), an electrolytic gold plating solution with a surfactant concentration of 3 mg / L (Example 4), an electrolytic gold plating solution with a surfactant concentration of 5 mg / L (Example 5), and an electrolytic gold plating solution with a surfactant concentration of 10 mg / L (Example 6) were prepared. The surface tension and the number of particles in the liquid were analyzed for these electrolytic gold plating solutions. The results are shown in Table 1. As shown in Table 1, the surface tension is less than 60 mN / m, and the number of particles is good.

[0047] Use these electrolytic gold plating solutions to perform electrolytic gold plating under the above conditions, form an electrolytic gold-plated film on the through hole, and then measure the film thickness (outermost surface and bottom) of the electrolytic gold-plated film. As a result, it is confirmed that the film thickness ratio (bottom / outermost surface) is more than 0.5, and the electrolytic gold-plated film is fully formed at the bottom of the through hole. In addition, electrolytic gold plating is performed on the substrate for hardness measurement under the above conditions to form an electrolytic gold-plated film, and then the hardness of the electrolytic gold-plated film is measured. As a result, a good result of more than 50Hv hardness after heating is obtained. In addition, the appearance of the obtained electrolytic gold-plated film is matte or semi-glossy. The above results are summarized and shown in Table 1.

[0048]

[0049] (Examples 7 to 12)

[0050] Using dodecylamine sulfate (cationic surfactant) as a surfactant, electrolytic gold plating solutions with a surfactant concentration of 0.01 mg / L (Example 7), an electrolytic gold plating solution with a surfactant concentration of 0.1 mg / L (Example 8), an electrolytic gold plating solution with a surfactant concentration of 1 mg / L (Example 9), an electrolytic gold plating solution with a surfactant concentration of 3 mg / L (Example 10), an electrolytic gold plating solution with a surfactant concentration of 5 mg / L (Example 11), and an electrolytic gold plating solution with a surfactant concentration of 10 mg / L (Example 12) were prepared. The surface tension and the number of particles in the liquid were analyzed for these electrolytic gold plating solutions. The results are shown in Table 1. As shown in Table 1, the surface tension is less than 60 mN / m, and the number of particles is good.

[0051] Use these electrolytic gold plating solutions to perform electrolytic gold plating under the above conditions, form an electrolytic gold-plated film on the through hole, and then measure the film thickness (outermost surface and bottom) of the electrolytic gold-plated film. As a result, it is confirmed that the film thickness ratio (bottom / outermost surface) is more than 0.5, and the electrolytic gold-plated film is fully formed at the bottom of the through hole. In addition, electrolytic gold plating is performed on the substrate for hardness measurement under the above conditions to form an electrolytic gold-plated film, and then the hardness of the electrolytic gold-plated film is measured. As a result, a good result of more than 50Hv hardness after heating is obtained. In addition, the appearance of the electrolytic gold-plated film is matte or semi-glossy. The above results are summarized and shown in Table 1.

[0052] (Examples 13 to 18)

[0053] Use of cetylpyridinium chloride Monohydrate (cationic surfactant) was used as a surfactant to prepare electrolytic gold plating solutions with a surfactant concentration of 0.01 mg / L (Example 13), a surfactant concentration of 0.1 mg / L (Example 14), a surfactant concentration of 1 mg / L (Example 15), a surfactant concentration of 3 mg / L (Example 16), a surfactant concentration of 5 mg / L (Example 17), and a surfactant concentration of 10 mg / L (Example 18). The surface tension and the number of particles in the liquid were analyzed for these electrolytic gold plating solutions. The results are shown in Table 1. As shown in Table 1, the surface tension is less than 60 mN / m, and the number of particles is good.

[0054] Use these electrolytic gold plating solutions to perform electrolytic gold plating under the above conditions, form an electrolytic gold-plated film on the through hole, and then measure the film thickness (outermost surface and bottom) of the electrolytic gold-plated film. As a result, it is confirmed that the film thickness ratio (bottom / outermost surface) is more than 0.5, and the electrolytic gold-plated film is fully formed at the bottom of the through hole. In addition, electrolytic gold plating is performed on the substrate for hardness measurement under the above conditions to form an electrolytic gold-plated film, and then the hardness of the electrolytic gold-plated film is measured. As a result, a good result of more than 50Hv hardness after heating is obtained. In addition, the appearance of the electrolytic gold-plated film is matte or semi-glossy. The above results are summarized and shown in Table 1.

[0055] (Comparative Examples 1 to 6)

[0056] Using sodium dodecylamine sulfate (anionic surfactant) as a surfactant, electrolytic gold plating solutions with a surfactant concentration of 0.01 mg / L (Comparative Example 1), a surfactant concentration of 0.1 mg / L (Comparative Example 2), a surfactant concentration of 1 mg / L (Comparative Example 3), a surfactant concentration of 3 mg / L (Comparative Example 4), a surfactant concentration of 5 mg / L (Comparative Example 5), and a surfactant concentration of 10 mg / L (Comparative Example 6) were prepared. The surface tension and the number of particles in the liquid were analyzed for these electrolytic gold plating solutions. The results are shown in Table 1. As shown in Table 1, the number of particles is poor.

[0057] Using these electrolytic gold plating solutions, electrolytic gold plating was performed under the above conditions to form an electrolytic gold plating film on the through hole, and then the film thickness (outermost surface and bottom) of the electrolytic gold plating film was measured. As a result, it was confirmed that the film thickness ratio (bottom / outermost surface) was less than 0.5, and the electrolytic gold plating film was not fully formed at the bottom of the through hole. The above results are summarized and shown in Table 1.

[0058] (Comparative Examples 7 to 10)

[0059] Using sodium dihexyl sulfosuccinate (anionic surfactant) as a surfactant, electrolytic gold plating solutions with a surfactant concentration of 0.01 mg / L (Comparative Example 7), a surfactant concentration of 1 mg / L (Comparative Example 8), a surfactant concentration of 3 mg / L (Comparative Example 9), and a surfactant concentration of 5 mg / L (Comparative Example 10) were prepared. The surface tension and the number of particles in these electrolytic gold plating solutions were analyzed. The results are shown in Table 1. As shown in Table 1, the number of particles was poor.

[0060] Using these electrolytic gold plating solutions, electrolytic gold plating was performed under the above conditions to form an electrolytic gold plating film on the through hole, and then the film thickness (outermost surface and bottom) of the electrolytic gold plating film was measured. As a result, it was confirmed that the film thickness ratio (bottom / outermost surface) was less than 0.5, and the electrolytic gold plating film was not fully formed at the bottom of the through hole. The above results are summarized and shown in Table 1.

[0061] (Comparative Examples 11 to 16)

[0062] Using lauryl dimethylamine acetic acid betaine (amphoteric surfactant) as a surfactant, electrolytic gold plating solutions with a surfactant concentration of 0.01 mg / L (Comparative Example 11), a surfactant concentration of 0.1 mg / L (Comparative Example 12), a surfactant concentration of 1 mg / L (Comparative Example 13), a surfactant concentration of 3 mg / L (Comparative Example 14), a surfactant concentration of 5 mg / L (Comparative Example 15), and a surfactant concentration of 10 mg / L (Comparative Example 15) were prepared. The surface tension and the number of particles in the liquid were analyzed for these electrolytic gold plating solutions. The results are shown in Table 1. As shown in Table 1, the surface tension shows a high value greater than 60 mN / m.

[0063] Using these electrolytic gold plating solutions, electrolytic gold plating was performed under the above conditions to form an electrolytic gold plating film on the through hole, and then the film thickness (outermost surface and bottom) of the electrolytic gold plating film was measured. As a result, it was confirmed that the film thickness ratio (bottom / outermost surface) was less than 0.5, and the electrolytic gold plating film was not fully formed at the bottom of the through hole. The above results are summarized and shown in Table 1.

Claims

1. A cyanide-free electrolytic gold plating solution, characterized in that: The cyanide-free electrolytic gold plating solution contains an alkali metal gold sulfite salt, a water-soluble amine, a crystal modifier and a cationic surfactant. The concentration of the cationic surfactant is 0.01 mg / L or more and 10 mg / L or less.

2. The cyanide-free electrolytic gold plating solution according to claim 1, wherein The cationic surfactant is a quaternary ammonium salt and / or an aliphatic amine.

3. The cyanide-free electrolytic gold plating solution according to claim 1 or 2, characterized in that: The surface tension of the cyanide-free electrolytic gold plating solution is less than 60 mN / m.

Citation Information

Patent Citations

  • Non-cyanogen based gold electroplating bath for forming bump

    JP2007092156A

  • Non-cyanogen type electrolytic gold plating bath for bump formation

    JP2008115450A

  • Non-cyanogen type electrolytic gold plating bath for bump forming

    CN101363128A

  • Cyanide-free silver-based composite plating solution, silver-based composite plating layer and preparation method thereof

    CN111235608A

  • Non cyanide gold plating bath for bump and preparation method of bump

    TW200928008A